Superconducting critical temperature elevated by intense magnetic fields - Z. Wu; H. Chen; T. I. Weinberger; A. Cabala; D. E. Graf; Y. Skourski; W. Xie; Y. Ling; Z. Zhu; V. Sechovský; M. Vališka; F. M. Grosche; et al. (Proceedings of the National Academy of Sciences, 2025)
Below a critical temperature T c , superconductors transport electrical charge without dissipative energy losses. The application of a magnetic field B generally acts to suppress T c , up to some critical field strength at which T c → 0 K. Here, we investigate magnetic field–induced superconductivity in high-quality specimens of the triplet superconductor candidate UTe 2 in pulsed magnetic fields up to B = 70 T. Strikingly, we find that this material has a higher T c when B > 40 T ( T c ≈ 2.4 K) than it does for B = 0 T ( T c = 2.1 K). This observation points to a fundamentally distinct mechanism for the formation of superconductivity at high B in UTe 2 compared to the case of B = 0 T.